N-doped CNT: distribution electron on different ratio N/C for oxygen reduction reaction - Nabila .A. Karim; Muhammad Syafiq Alias; Siti Kartom Kamarudin; Norilhamiah Yahya (Penerbit Universiti Kebangsaan Malaysia, 2020)
Carbon nanotubes (CNTs) have the advantage to improve electrochemical fuel cell reactions by increasing the dispersion of nanoparticles as well as having high strength in mechanical and electrical properties. Therefore, this study presents the comparison of nitrogen doped CNT and other doping heteroatom on CNT as a catalyst support for application in the Direct Liquid Fuel Cell (DLFC). The doping ratio in CNT was conducted to determine the effect of the oxygen reduction reaction. In addition, the effect of CNT diameter in oxygen adsorption also has been tested. The models and calculations were done using density functional theory (DFT). The result showed that the ratio of N/C is decreases as the diameter of CNT decreases. The value is even dropped as the unit cell is increased to 1x1x2. The band gap value of CNT before doping is higher compared to after nitrogen doping. While increasing the diameter of doped CNT has increased the mulliken charge distribution and thus make the model more stable. In the adsorption energy of molecule oxygen, the 1x1x2 unit cell of CNT and large diameter show a remarkable and stable compared to in 1x1x1 unit cell and small diameter of CNT. Thus, the adsorption energy of the oxygen molecule shows a more stable value in the low doping ratio and high CNT diameter compared to a high doping ratio and a small diameter of the CNT. This result shows the potential of the CNT in helping to improve electrochemical reaction in DLFC.